2010
DOI: 10.1007/s10295-010-0887-2
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of Bacillus sp. obtained from an Algerian oilfield and chemical biocide THPS against sulfate-reducing bacteria consortium inducing corrosion in the oil industry

Abstract: The present study enlightens the role of the antagonistic potential of nonpathogenic strain B21 against sulfate-reducing bacteria (SRB) consortium. The inhibitor effects of strain B21 were compared with those of the chemical biocide tetrakishydroxymethylphosphonium sulfate (THPS), generally used in the petroleum industry. The biological inhibitor exhibited much better and effective performance. Growth of SRB in coculture with bacteria strain B21 antagonist exhibited decline in SRB growth, reduction in producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Gana et al . [46] reported that injection waters sampled from Algerian oilfields were characterized by mesophilic temperature, low salinity, neutral pH and high concentration of SO 4 2− ; this is consistent with our data.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Gana et al . [46] reported that injection waters sampled from Algerian oilfields were characterized by mesophilic temperature, low salinity, neutral pH and high concentration of SO 4 2− ; this is consistent with our data.…”
Section: Resultssupporting
confidence: 93%
“…Water characteristics of non-flooded wells, sampled in this study (high temperature, neutral to acidic pH, high salts, chloride-type and alkaline cations such as calcium and barium) were consistent with the previously reported data in others oilfields [20], [45], [46].…”
Section: Resultssupporting
confidence: 91%
“…The same strain has been shown to inhibit Desulfosporosinus orientis biofilms in situ [66]. The Bacillus strain B21, which was isolated from injection water obtained from an Algerian Sahara oilfield, was recently shown to inhibit a SRB consortium in co-culture [67] better than the biocide tetrakis hydroxymethyl phosphonium sulphate - THPS. However, the mode of action of strain B21 against sulfate reducing bacteria growth was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…) that shows antibacterial properties, especially against sulfate‐reducing bacteria (SRB) . This feature makes THPS suitable not only for traditional water treatment but also in oilfield applications to avoid corrosion and clogging of metallic ducts by iron sulfides due to the formation of H 2 S by SRB activity .…”
Section: Introductionmentioning
confidence: 99%